A critical assessment of whether shale gas extraction (hydraulic fracturing) conforms with the underlying principle of sustainable development - Van der Walt, Robert (Institute of Marine and Environmental Law, 2016)
It is estimated that the eighth largest resource of shale gas reserves in the world is in South Africa. The proposed extraction of shale gas using hydraulic fracturing requires great volumes of water and many hazardous chemicals which also risks water pollution. This can add to water stress because the Karoo is a semi-arid and drought prone region. In this study I will, after taking into account that South Africa receives an average annual rainfall of almost half the international annual rainfall, answer the question on whether the fracking process is a risk worth taking by measuring the process to the underlying principle of sustainable development. The world is faced with challenges in all three dimensions of sustainable development (economic, social and environmental). More than 1 billion people are still living in extreme poverty, and income inequality within and among many countries has been rising; at the same time, unsustainable consumption and production patterns have resulted in huge economic and social costs and may endanger life on the planet. In this minor dissertation, sustainable development will be defined explained and examined, looking at environmental sustainability as well as an in depth look at the underlying principles of sustainable development, examining the advantages and disadvantages of each. However, because the first step in making sustainable development more concrete is the formulation of legal principles, I will analyse the South African legal framework governing fracking as a process. In this minor dissertation it is found that the disadvantages outweigh the advantages within the three spheres of sustainable development.